Using CLDFBench and PyLexibank on Windows (Computer-Assisted Language Comparison in Practice: Tutorials on Computational Approaches to the History and Diversity of Languages, 2024)
Using tools such as CLDFBench and PyLexibank, datasets can be converted into Cross-Linguistic Data Formats (CLDF), offering a standardized and interoperable representation of linguistic data. While these tools are powerful, lifting datasets to CLDF can present unique challenges for Windows users due to idiosyncrasies in the Windows operating system. Although CLDFBench and PyLexibank are compatible with Windows, certain workarounds may be necessary to address system-specific issues. This guide aims to demonstrate how CLDFBench and PyLexibank can be effectively installed and used on a Windows computer to lift a dataset to CLDF.
Keywords: CLDF; CLDFBench; PyLexibank; Lexibank; Windows; operating system; CLDF conversion